Ethical and Corporate Social Responsibility Implications of Artificial Intelligence Application for the Detection and Prevention of Financial Fraud - Lindez-Macarro, María Elena; Villalba-Romero, Felix (IGI, 2025)
This analysis provides the essential principles for under standing the use of AI in the detection of financial fraud, assessing its effectiveness, and examining the tools used to understand the conceptual framework within which ethics and CRS are defined in the application of AI.
https://www.igi-global.com/about/rights-permissions/content-reuse/
Keywords: Responsabilidad social de la empresa - Aspectos morales; Inteligencia artificial; AI Principles; Financial fraud; Ethics; AI conceptual framework